The Role of Brand Image in Mediating the Influence of Product Completeness and Price Perception on Consumer Repurchase Intention of Clandys in Gianyar - Cok. Gd Unadita Yana; Tjokorda Gde Raka Sukawati; Ni Nyoman Rsi Respati (PT FORMOSA CENDEKIA GLOBAL, 2025)
Companies must constantly innovate in the retail industry to stay ahead of the competition and keep customers. Customer satisfaction at Clandys Grosir in Gianyar is impacted by issues including diminishing sales and uneven product completeness. This study is to examine how consumers' perceptions of price and product completeness affect their desire to repurchase at Clandys in Gianyar, and how brand image functions as a mediator in this relationship. The Sobel test and path analysis are two components of the quantitative research methodology. There were 130 responders in all, and the sample was chosen using a non-probability sampling technique. The findings indicate that the impact of price perception and product completeness on repurchase intention is considerably mediated by brand image. These results suggest that consumers' propensity to repurchase can be increased by a strong brand image, well-maintained product completeness, and a favorable price perception. In order to boost customer repurchase intention, Clandy's should focus more on these elements in their marketing tactics, according to the research's practical implications.